Henry Barrett Learned papers - Learned, Henry Barrett, 1868-1931.; Learned, Henry Barrett, 1868-1931.
Chiefly notes and related materials gathered by Learned for revision of his book The President's Cabinet: Studies in the Origin, Formation and Structure of an American Institution (1912) and an unpublished history of the vice presidency. Includes a typescript of The President's Cabinet with notations. Also includes papers relating to the International Congress of Historical Sciences in 1923 and 1928, Learned's seminars at Stanford University, and a movement between 1914 and 1917 to reform the American Historical Association.
Historian and professor at Stanford University.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Cabinet officers; History -- Societies, etc; Vice-Presidents -- United States; Stanford University -- Faculty; American Historical Association; United States -- Politics and government; Educators; Historians